Mussel‐inspired green synthesis of Ag‐coated polydopamine microspheres for selective antibacterial performance. (3rd April 2019) - Guo, Aiying; Mu, Qianzhu; Cai, Aijun; Wang, Xiuping
Abstract : Inspired by mussels, the antimicrobial Ag‐coated polydopamine microspheres (Ag‐coated PDA MSs) composites are synthesised through one‐pot method. Ag nanoparticles (NPs) are easily generated using PDA MSs as green reducing agents, and are well‐dispersed on the surface of PDA MSs at the same time. The morphology and structure of the Ag‐coated PDA MSs are characterised by X‐ray diffraction, X‐ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. The Ag‐coated PDA MSs exhibit selective antibacterial activity towards S. aureus . Due to the elevated intracellular reactive oxygen species level, the majority of S. aureus cells are killed, however, the growth of E. coli is not affected evidently in the same condition.